A Nation of Investors or a Procession of Fools? Reevaluating the Behavior of Britain's Shareholding Population through the Prism of the Interwar Sharepushing Crime Wave. (28th August 2018) - HOLLOW, MATTHEW
Abstract : In recent years, there has been a notable increase in the amount of scholarship on the history of shareholding in Britain. One area that still remains relatively unexplored, however, is the problematic issue of how British investors actually went about the process of choosing their respective investments. The purpose of this article is to make a start at redressing this gap by using the (perceived) sharepushing crime wave that swept across Britain during the interwar period as a prism through which to evaluate the behavior of Britain's shareholding population at this time. Ultimately, what it suggests is that, while the interwar British investors may well have had far more potential sources of advice and information open to them than their nineteenth-century forebears, this did not necessarily mean that they were any better informed about the workings of the British securities market.